2006
DOI: 10.4049/jimmunol.177.11.8037
|View full text |Cite
|
Sign up to set email alerts
|

An HLA-A2.1-Transgenic Rabbit Model to Study Immunity to Papillomavirus Infection

Abstract: We have established several HLA-A2.1-transgenic rabbit lines to provide a host to study CD8+ T cell responses during virus infections. HLA-A2.1 protein expression was detected on cell surfaces within various organ tissues. Continuous cultured cells from these transgenic rabbits were capable of presenting both endogenous and exogenous HLA-A2.1-restricted epitopes to an HLA-A2.1-restricted epitope-specific CTL clone. A DNA vaccine containing an HLA-A2.1-restricted human papillomavirus type 16 E7 epitope (amino a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
71
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(72 citation statements)
references
References 43 publications
1
71
0
Order By: Relevance
“…Our previous studies have demonstrated that a newly established HLA-A2.1 transgenic rabbit model generated a strong immune response to a well-known HLA-A2.1 restricted epitope from HPV16 E7 in vivo [1]. In this paper, we extend these studies to test the immunogenicity of some naturally existing HLA-A2.1 restricted epitopes in CRPVE1.…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…Our previous studies have demonstrated that a newly established HLA-A2.1 transgenic rabbit model generated a strong immune response to a well-known HLA-A2.1 restricted epitope from HPV16 E7 in vivo [1]. In this paper, we extend these studies to test the immunogenicity of some naturally existing HLA-A2.1 restricted epitopes in CRPVE1.…”
Section: Introductionmentioning
confidence: 89%
“…Although E1 is mostly expressed in the upper basal layer of the skin and is not considered as an effective candidate HPV vaccine, several studies have demonstrated that E1 vaccination can either induce regression or provide protection against virus infection in different animal models [7][8][9][10][11][12][13]. We chose five naturally existing HLAA2.1 restricted epitopes from CRPVE1 based on an online MHCI epitope prediction software program to design a multivalent epitope DNA vaccine [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…HPV 16 peptides E1-LLQQYCLYL254-262 [34], E5-FLLCFCVLL15-23, VLLCVCLLI21-29 [35], E6-KLPQLCTEL18-26 [36,37] and E7-TLHEYMLDL7-15 [38] are known CTL epitopes. E7-LLMGTLGIV82-90 was known to induce the cellular response in HLA A2.1 rabbit model [39] and reduced tumor burden in aged mice [40]. E6-KLPDLCTEL13-22 [41] and E7-TLQDIVLHL [7][8][9][10][11][12][13][14][15] One of the predicted peptides, QLFVTVVDT [42] were proved to be CTL epitopes for HPV 18.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies on viral immunity using rabbit MHC are uninformative in the context of human immune responses. To assess immunity in the context of a human MHC allele, a transgenic rabbit model expressing HLA-A*0201 was generated, 64 which is particularly advantageous because epitopes from HPV proteins can be engineered into similar genes in the CRPV genome, which retains the ability to generate papillomas. This model is very interesting and appropriate to evaluate anti-HPV immune responses after natural infection.…”
Section: Rabbit Modelsmentioning
confidence: 99%